Asymmetry in the aging brain: A narrative review of cortical activation patterns and implications for motor function. Issue 4 (3rd July 2020) - Hill, Christopher; Van Gemmert, Arend W. A.; Fang, Qun; Hou, Lijuan; Wang, Jun; Pan, Zhujun
ABSTRACT: Age-related changes have been identified in neural and motor level. A prominent change is reduced asymmetry in cortical activation as well as motor performance. Cortical activation models have been established based on cognitive research utilizing neuroimaging techniques to explain age-related effects on neural recruitment and reduced brain asymmetry. Recently, researchers in motor behaviour attempted to apply the models to explain motor pattern changes in aging and proposed compensation as the mechanism of the reduced motor asymmetry in older adults. Age-related alterations in movement patterns and brain activations seem to be correlated. However, based on the literature search result, no direct evidence substantiates the connection between reduced brain asymmetry and motor asymmetry in older adults. Therefore, a theoretical gap was identified. The theoretical gap exists because either neuroimaging studies have not considered motor asymmetry or motor asymmetry studies have not integrated neuroimaging techniques into study designs. Answering the research question can be valuable to both research and clinical practice. With the mechanisms of brain activation patterns during motor tasks in an aging population being better understood, protocols developed upon the new understandings can be applied to current motor interventions and better maintain the longevity of motor function of older adults.